Investigating the effect of alumina nanoparticles on heat transfer and entropy generation inside a square enclosure equipped with two inclined blades under magnetic field. (March 2019) - Al-Rashed, Abdullah A.A.A.
Highlights: Numerical investigation of entropy generation and free convection of alumina nanofluid. Enclosure with two inclined blades on the vertical walls under a constant magnetic field. Evaluating effects of Hartmann, Rayleigh, fieldangle, concentration, thermal conductivity and angles of the blades. The highest heat transfer rate occurs at the magnetic field angle of 60°. With increased volume percentage of nanofluids, heat transfer rate increases. Abstract: In this study, entropy generation and free convection of alumina nanofluid inside an enclosure with two inclined blades on the vertical walls are studied numerically. The blades in the cavity are capable of being slipped and tilted by changing their angles. The enclosure is under the influence of a constant magnetic field. The lower part is exposed to non-uniform sinusoidal temperature and the upper wall is insulated. The governing equations were solved using Simple algorithm simultaneously. In this study, the effects of changes in Hartmann numbers, Rayleigh number, the magnetic field angle, nanoparticle volume percentage, thermal conductivity coefficient of the blades, and blades angles on flow field, temperature, heat transfer rate, and entropy were investigated. The findings show that with growing Rayleigh number and reducing Hartmann number, heat transfer rate and entropy generation increase. In lower Rayleigh numbers, the highest transfer rate occurs at the blade angle of −45° and in higher Rayleigh numbers, this occurs at the blade angle of 0°. With increasing blade thermal conductivity, first, the Nusselt number increases and finally, no change occurs. The highest heat transfer rate occurs at the magnetic field angle of 60°. With increasing volume percentage of nanofluids, heat transfer rate increases. With augmenting Rayleigh and Hartmann numbers, the Bejan number falls.